PENGEMBANGAN SUMBER BELAJAR BERBASIS WEB PADA MATA PELAJARAN PAI DI SMA NEGERI 1 TENJOLAYA BOGOR - Abidin, Zaenal; Fajriyah, Ayi (STIT Sirojul Falah Bogor, 2024)
This research is based on the development of technology and information that has developed greatly towards the world of education. Utilization of the web as a learning medium in accordance with the learning styles of students who are heading towards the digital era, web-based learning is a learning activity that utilizes website media that can be accessed through the internet network. internet network access provided by the school then the web-based learning media can be used by the teacher as one of the learning media where the teacher still uses learning in every learning. This research focuses on the problem of How to Develop WEB-Based Learning Media in Islamic Religious Education Subjects at SMAN 1 Tenjolaya Bogor.This research studies: 1) Producing web-based learning media on Islamic Religious Education subjects; 2) Describe the results of student responses to the use of web-based learning media in Islamic Religious Education subjects Related to this research is research and development (Research & Development) or R&D related to products, instructional media development, using ADDIE models which include Analysis, Design, Development, Implementation, and Evaluation. Research data obtained through observation, questionnaire, and documentation. Furthermore, data analysis using the results score from the validation of media experts, material experts and student responses to web-based learning media. The results of the research show: 1) the development by the researcher carries out student character analysis, media analysis, and data analysis of media and material experts, then designs the media with a web site application that contains a blog, media development on materials, desired products, validation, tests try to do 28 students of class X, implement the developed media then given to the teacher to be used for students then the researcher gives a questionnaire to students about perceptions of the developed media, then a further evaluation of the media based on the assessment of students and the media developed. 2) Inviting students about Learning Media by providing a questionnaire of 28 students using web-based learning media that are close to God, the media developed